Cover Feature: Nickel (0) Complexes as Promising Chemosensors for Detecting the "Cork Taint" in Wine (Eur. J. Inorg. Chem. 9/2022). Issue 9 (1st March 2022) - Damiano, Caterina; Intrieri, Daniela; Sonzini, Paolo; Rizzato, Silvia; Di Natale, Corrado; Paolesse, Roberto; Gallo, Emma
Abstract : The Cover Feature shows the oxidative addition of 2, 4, 6‐trichloroanisole (TCA) by the simple Ni(0)(BINAP)(η 2 ‐PhCN) complex, which represents an appealing strategy for the chemical detection of the cork taint of wine. The present study can pave the way for realizing a low‐cost chemosensor that enables the identification of TCA‐contaminated cork stoppers by means of UV‐visible spectroscopic analysis. More information can be found in the Research Article by E. Gallo and co‐workers .